2016
DOI: 10.1088/1367-2630/18/10/105006
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of electrons and neutral particles in radio-frequency transformer coupled plasma Hion source at Seoul National University

Abstract: In volume production H − ion sources, control of electron temperature is essential due to its close correlation with the generation of vibrationally-excited hydrogen molecules in the driver region as well as the generation of H − ions by dissociative attachment in the extraction region. In the ion source group at Seoul National University (SNU) in Korea, a lot of research effort has been made to the development of a volume production H − ion source based on radio-frequency (RF) transformercoupled plasma (TCP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…From another point of view, our results indicate that it is possible to control the eepf within the magnetically expanding plasma generated by the ECR or helicon sources by changing the bounce region of confined electrons according to the magnetic field conditions. It is meaningful that these characteristics can play a leading role in the generation of specific radical and ion species in the plasma processing, in which the spatial distribution of eepf is a decisive factor [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…From another point of view, our results indicate that it is possible to control the eepf within the magnetically expanding plasma generated by the ECR or helicon sources by changing the bounce region of confined electrons according to the magnetic field conditions. It is meaningful that these characteristics can play a leading role in the generation of specific radical and ion species in the plasma processing, in which the spatial distribution of eepf is a decisive factor [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Gabriel et al mentioned rotational temperature in the 3000-4000 K range 95 while Briefi et al indicated a two-temperature Boltzmann distribution with a low (564 K) and a high (5440 K) component 56 and Wagner et al 66 showed up lower rotational temperature, 380 K. In our reactor, in plasma-OFF condition it appears slightly above the temperature of the temperature-regulated walls of the reactor (283 K). In plasma-ON condition, it is surprisingly low even if at low pressure (8 µbar) and low electron density (∼3×10 15 m −3 ) energy transfer between electrons and neutrals through inelastic collisions is weak 96 . Péalat et al 67 measured similar rotational temperature in a plasma of analogous density and highlighted the effect of passive gas surrounding the plasma, mentioned in 4.1, on the rotational temperature of the low ro-vibrational levels (v = 0, J 3) attributed to the plasma volume.…”
Section: Distribution Of Energy Over Rotational and Translational Of The D2mentioning
confidence: 99%
“…From semiconductor processes to electric propulsion in space, most plasma sources are operated with an external magnetic field to achieve high plasma density [1][2][3][4][5][6]. The magnetic field applied to plasma devices is in the range of tens to hundreds of gauss, so that light electrons are fully magnetized while the Larmor radius of heavy ions often exceeds the source dimensions.…”
Section: Introductionmentioning
confidence: 99%